Better to grow or better to improve? Measuring environmental efficiency in OECD countries with a Stochastic Environmental Kuznets Frontier - Oleg Badunenko; Marzio Galeotti; Lester C. Hunt (Fondazione Eni Enrico Mattei (FEEM), 2021)
The standard approach to the Environmental Kuznets Curve (EKC) holds that as a country develops and GDP per capita grows environmental degradation initially increases but eventually it reaches a turning point where environmental degradation begins to decline. Environmental degradation takes many forms, one of them being emissions of harmful gases. According to the EKC concept, a country can reduce emissions by `growing'. The standard approach implicitly assumes that a country emits as little as possible for its economic development, whereas in reality, a country might emit above the best attainable level of emissions. Therefore, emissions could be reduced before and after the turning point by becoming more environmentally efficient – i.e., `improving' the emissions level. This article proposes a Stochastic Environmental Kuznets Frontier (SEKF) which is estimated for CO2 emissions for OECD countries and used to benchmark each country before and after the turning point differently, thus, indicating how a country could `grow' and/or `improve' to reduce its CO2 emissions. Additionally, we analyse the role of the stringency of environmental policies in reducing a country's carbon inefficiency measured by the distance from the benchmark EKC and find widespread carbon inefficiencies that could be reduced by more stringent market-based environmental policies.
Keywords: O44; Q56; Q54; C13; C33; 330; Environment and growth; Environmental Kuznets Curve; CO2 emissions; Panel data; OECD countries; Stochastic frontier approach; Stochastic Environmental Kuznets Frontier; Environmental Policy Stringency